2001
DOI: 10.1094/phyto.2001.91.7.687
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of the Root-Knot Nematode Meloidogyne javanica by Trichoderma harzianum

Abstract: The fungal biocontrol agent, Trichoderma harzianum, was evaluated for its potential to control the root-knot nematode Meloidogyne javanica. In greenhouse experiments, root galling was reduced and top fresh weight increased in nematode-infected tomatoes following soil pretreatment with Trichoderma peat-bran preparations. The use of a proteinase Prb1-transformed line (P-2) that contains multiple copies of this gene improved biocontrol activity in the greenhouse experiments compared with the nontransformed wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(199 citation statements)
references
References 19 publications
11
162
0
13
Order By: Relevance
“…Our study is in accordance with previous experiments by others (Dababat and Sikora 2007a, b;Martinuz et al 2012b;Sikora et al 2008). With respect to reduced female fecundity, Martinuz et al (2012a) and Sharon et al (2001) also reported that fewer adult rootknot nematodes had infected tomato roots and also fewer nematodes had reached the female stage 28 days after M. incognita and M. javanica inoculation in endophytetreated plants.…”
Section: Fungal Endophytes With Biocontrol Potentialsupporting
confidence: 93%
“…Our study is in accordance with previous experiments by others (Dababat and Sikora 2007a, b;Martinuz et al 2012b;Sikora et al 2008). With respect to reduced female fecundity, Martinuz et al (2012a) and Sharon et al (2001) also reported that fewer adult rootknot nematodes had infected tomato roots and also fewer nematodes had reached the female stage 28 days after M. incognita and M. javanica inoculation in endophytetreated plants.…”
Section: Fungal Endophytes With Biocontrol Potentialsupporting
confidence: 93%
“…The relatively high efficacy demonstrated by T. harzianum f 1 (Table 1) supports the need for further experimentations and development. Increase in the efficacy of the fungi appears possible when such biocontrol agents are integrated with organic amendments such as oil cakes (Parvatha Reddy et al, 1996) and wheat branpeat preparations (Sharon et al, 2001). Eventually, although chemical nematicide viz.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in root-knot development could be attributed to poor penetration of the second stage juveniles and later retardation in their activities, for example feeding and/or reproduction as suggested by Abdi [72]. Nematotoxic compounds especially the Azadirachtin released through gradual decomposition of the neem seeds [29] and suppress nematode populations throughout the whole period of the nursery stage. Nematode population in nematode + fungus treatment was 532 but L. camara has decreased population to 303.…”
Section: Final Nematode Population and Reproduction Factormentioning
confidence: 99%
“…Trichoderma viride which were reduced egg-hatching [25] and trade formulations have also proven to be efficacious in tropical greenhouse conditions [26]. Some species of Trichoderma have been used widely as bio-control agents against soil-borne plant diseases [27] and also they have activity towards root-knot nematode [28,29]. Al Kader [30] reported a high nematicidal effect of the fungus Paecilomyces lilacinus culture filtrate on J2 of M. incognita, with 99% of J2 immobilized after 2 days of treatment.…”
Section: Introductionmentioning
confidence: 99%